The Effects of Government Spending Under Limited Capital Mobility - Shen, Wenyi; Yang, Susan (Washington, D.C. : International Monetary Fund, 2012)
This paper studies the effects of government spending under limited international capital mobility, as featured by most developing countries. While external financing of government debt mitigates the crowding-out effect, it generates real appreciation, which contracts traded output and lowers the fiscal multiplier in the short run. The decline of the multiplier is larger when facing debt-elastic country risk premia. Also, government spending is more expansionary with more home bias in government purchases, more sectoral rigidities, and a less flexible exchange rate. Whether the twin-deficit hypothesis holds depends crucially on the extent to which government deficits are financed externally.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet